A Dynamic Submerging Motion Model of the Hybrid–Propelled Unmanned Underwater Vehicle: Simulation and Experimental Verification - Talarczyk Tomasz (International Journal of Applied Mathematics and Computer Science, 2023)
Hybrid propulsion in underwater vehicles is the new idea of combining conventional propulsion systems such as screw propellers with other kinds of propulsion like oscillating biomimetic fins, glider wings or jet thrusters. Each of these propulsion systems has its own benefits and drawbacks, and the goal is to have them complement each other in certain conditions. This paper covers the topic of a dynamic model of the pitch and heave motion of the HUUV (hybrid unmanned underwater vehicle) using screw propellers and biomimetic lateral fins. Firstly, the simulation model of the vehicle performing depth and pitch change is presented. Secondly, the vehicle’s hydrodynamic coefficients obtained from CFD simulations are discussed. Thirdly, the results of the HUUV experimental studies in a swimming pool are presented. Lastly, simulation results are compared with those of the experiment to verify the correctness of the model. The vehicle’s motion in the swimming pool during the experiments was recorded using a submerged camcorder and then analysed using the Tracker software.